Prototype Pendeteksi Asap Kebakaran Dan Kebocoran Gas Berbasis Arduino Uno Dengan Menggunakan Sensor Gas MQ-5 - Fitriatin Nisa Az Zahro; Reni Rahmadewi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Fire is an event where small fires or large fires start that we don't plan and cause a lot of losses around it. Fire is a tragedy that often occurs in Indonesia. There are various factors that can trigger a fire including human negligence, natural factors and intentional factors. One type of fire that often occurs in Indonesia is a type of fire caused by human negligence, namely house fires where house fires can cause large losses, both material losses and fatalities. In 2020-2022 there will be lots of house fires caused by explosions of LPG gas where the initial cause of these explosions was not caused by gas cylinders but caused by devices from these gas cylinders such as hoses and regulators. Through this incident, we need a fire detection system that can detect the presence of leaking gas smoke or fire in the house. In this study the authors will create a fire detection system using Arduino Uno R3 as a microcontroller connected by an MQ5 gas sensor as an input that can detect the presence of methane and butane which will then issue an output in the form of a red LED, a green LED and a 5v buzzer as a reminder alarm.